2010
DOI: 10.4103/0019-5413.65148
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical features and magnetic resonance imaging findings in lumbar disc prolapse

Abstract: Background:Lumbar disc prolapse is one of the common causes of low back pain seen in the working population. There are contradictorty reports regarding the clinical significance of various magnetic resonance imaging (MRI) findings observed in these patients. The study was conducted to correlate the abnormalities observed on MRI and clinical features of lumbar disc prolapse.Materials and Methods:119 clinically diagnosed patients with lumbar disc prolapse were included in the study. Clinical evaluation included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 13 publications
6
27
0
Order By: Relevance
“…This clearly shows that MRI evidence of nerve root compression is more likely to produce symptoms. 1 In our study, MRIvisible nerve root contact/compression produce symptomatic levels in 86.4% (51 out of 59 levels), with foramen/lateral recess compromise produce symptomatic levels in 44.4% and those without neural foramen compromise (TSC) produce sympto -matic levels in 7.4% cases, which is almost similar to above study finding.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This clearly shows that MRI evidence of nerve root compression is more likely to produce symptoms. 1 In our study, MRIvisible nerve root contact/compression produce symptomatic levels in 86.4% (51 out of 59 levels), with foramen/lateral recess compromise produce symptomatic levels in 44.4% and those without neural foramen compromise (TSC) produce sympto -matic levels in 7.4% cases, which is almost similar to above study finding.…”
Section: Discussionsupporting
confidence: 89%
“…1 The clinically significant sciatica due to disc prolapse is 4-6%. 2 In 85% of cases, no specific diagnosis can be made.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have analyzed the correlation between clinical findings and MRI scans for lumbar disc herniation [61112]. To our knowledge, the present study is the first to extend this correlation to intraoperative findings.…”
Section: Discussionmentioning
confidence: 59%
“…MRI scans are available in various magnetic field strengths, with 1.5 Tesla being the most commonly used in India. Several studies have reported on the high sensitivity of this imaging modality [45678]. However, MRI studies in selected volunteers have also shown up to a 36% incidence of disc protrusion and extrusion in patients without symptoms, thus highlighting their low predictive value for the development of back and leg pain [910].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation